Study on Goitre In The Villages of Sirajgonj In Bangladesh (KYAMC Journal, 2017)
A total of 551 subjects were studied, 363 males and 188 females in some villages in Sirajgonj. The purpose of the study was to unravel the relation of goitre to intake of iodized-salt, mustard oil and cabbage. In our study the prevalence of goitre was 28.13%, in which the goitre of grade 1 and grade 2 was 21.96% and 6.17% respectively. In our study males were suffering more than the females. In this study goitre prevalence in those taking iodized salt was 28.57% and in those taking non-iodized salt was 28.05%. It is wonder to note that after more than two decades of enacting iodized salt more than 80% took non-iodized salt and even then the prevalence of goitre in the two groups were almost identical, with utter surprise goitre prevalence was more in those who took iodized salt. In this study goitre prevalence in those taking mustard oil was 28.6% and in those taking non-mustard oil was 24.14%. Goitre prevalence was much more in those who took mustard oil than those who took non-mustard oil. In this study goitre prevalence in those taking cabbage was 28.12% and in those taking non-cabbage was 28.21%.KYAMC Journal Vol. 5, No.-2, Jan 2015, Page 524-526